Juozas Tumas’ Ministry in the Diocese of Samogitia (Telšiai) in the Late 19th Century - Žaltkauskaitė, Vilma (Colloquia, 2020)
The author of the article analyzes the ministry of the Roman Catholic priest Juozas Tumas in the Diocese of Samogitia (Telšiai) in the late 19th century and discusses his position in the hierarchy of the local Church at that time. The article covers the years that Tumas spent in the Samogitian (Telšiai) Seminary in Kaunas (1888-1893) and his first clerical appointment in Mintauja (Jelgava) (1894-1895). The policy of secular government towards the Roman Catholic clergy is also discussed in the article. The author uses several sources, such as documents of the Roman Catholic Church and secular government, as well as ego-documents. She clarifies certain historiographical details that have been prevalent in the research of Tumas’s biography, and interprets new archival data. In the conclusions, the author of the article argues that from the very first year, Tumas belonged to a subgroup of students who constituted a minority in the seminary. The subgroup was characterized by higher education acquired in gymnasiums and progymnasiums. It also stood out for its social attitudes. Its members were active in the society and had been critical of the ecclesiastical authority and the state which favored the Orthodox Church. In the context of the appointments of other newly ordained priests, Tumas’ work in Mintauja did not stand out.
Keywords: Juozas Tumas; ministry; Roman Catholic priest; , Diocese of Samogitia (Telšiai)